Jews in the News – Representations of Judaism and the Jewish Minority in the Norwegian Contemporary Press. Issue 1 (2nd January 2016) - Døving, Cora Alexa
ABSTRACT: This article provides an analysis of how Jewish rituals and Jews as a minority group are represented and debated in the Norwegian press: How is "news about the Jews" framed by the media? Which discourses dominate the debates? Are notions of what it "takes to be Norwegian" put forward in these cases? The article is also an analysis of Jewish voices in the press, and based on the fact that Jewish advocates refer to minority-based legal rights suggests that the Jewish minority benefits from the use of a broader international human rights discussion in the press. I claim that a multicultural discourse provides the Jewish minority with language that makes it possible to argue for cultural rights without referring to Jewishness; offering protection against a general fear of anti-Semitism.